A check list of the world genera of the family Chloropidae (Diptera, Cyclorrhapha, Muscomorpha) - Nartshuk, Emilia P. (Zootaxa, 2012)
A check list of the world genera of the family Chloropidae (Diptera, Cyclorrhapha, Muscomorpha) reflects all generic namesand nomenclature changes published before 2010. It includes 204 valid genera: 2 fossils, 4 of Siphonellopsinae, 14 of Rhode-siellinae, 109 of Oscinellinae, 75 of Chloropinae and 138 subgenera and synonyms. Chloropid genera were described by 67 authors.